URGENSI MANAJEMEN KEUANGAN & MODEL PENGANGARAN PENDIDIKAN - Hanifah Nur Aini; Anne Effane (KARIMAH TAUHID, 2023)
Urgency School financial management is very important to classify school needs. Then there is an urgency for financial management and a clear and appropriate budgeting model that will affect school operations and education in these schools. From the urgency and the existing budgeting model, supervision of financial management is carried out which needs to be done to minimize errors that may occur. The purpose of this article is to find out how the Urgency of Financial Management and the Educational Budgeting Model are applied to find out how supervision is in financial management. Data collection is in the form of observations from various existing sources. The results of the analysis show that the results of the urgency and the Budgeting Model are carried out by managing school finances in carrying out the budget plan that has gone very well. This is indicated by several activity plans that are realized in accordance with expectations, namely transparent, accountable, effective and efficient. In addition, supervision of financial management is running well. The synergy between the school and the community is well established to build